2014
DOI: 10.1007/s00430-014-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 immune response to P30 and ROP18 peptides in human toxoplasmosis

Abstract: We determined the specific lymphocyte proliferative response and cytokine profile production regarding Toxoplasma P30 (2017 from virulent and non-virulent strain) and ROP18 protein-derived peptides (from clonal lineages I, II and III) in 19 patients having ocular toxoplasmosis, five suffering chronic asymptomatic infection, nine with congenital toxoplasmosis and eight Toxoplasma negative people. A Beckman Coulter FC500 flow cytometer was used for determining antigen-specific T cells (CD3+ CD4+ or CD3+ CD8+ cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
2
18
0
3
Order By: Relevance
“…Although the eye has immune privilege, the ocular immune response is connected with the peripheral response. We previously demonstrated that patients with ocular toxoplasmosis have different peripheral immune responses compared to those of patients without ocular involvement (9). Both retina and brain are damaged by Toxoplasma infection in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the eye has immune privilege, the ocular immune response is connected with the peripheral response. We previously demonstrated that patients with ocular toxoplasmosis have different peripheral immune responses compared to those of patients without ocular involvement (9). Both retina and brain are damaged by Toxoplasma infection in humans.…”
Section: Discussionmentioning
confidence: 99%
“…OT is characterized by intraocular inflammation and is the most common clinical manifestation of toxoplasmosis (7). Particularly, OT causes severe pathology in the eye in South America that is more severe than in other parts of the world, and it is characterized by deviated T helper 2 (Th2) immune responses (8,9). Lesions can originate both from congenital infection and from infections acquired after birth (10,11).…”
mentioning
confidence: 99%
“…Recently, scientists in Colombia have attempted to correlate severity of clinical toxoplasmosis in patients with genetic make of the strain and host responses (cytokine production), and found that the virulent allele of T. gondii ROP18 in ocular toxoplasmosis was correlated with severe ocular inflammatory response [ 98 ]. This study additionally found that the cytokine profile in Colombian patients with ocular toxoplasmosis was deviated to a Th2 profile [ 99 ]; instead, French patients had a Th1 preferential response [ 100 ]. Altogether, these results indicate that some Colombian strains cause more severe ocular toxoplasmosis due to an inhibition of the protective effect of IFN-γ.…”
Section: Reviewmentioning
confidence: 99%
“…In the present study, oral infections of sheep with T. gondii tissue cysts were performed to determine the entry site and subsequent distribution of the parasite following the natural infection route. Furthermore, we monitored the local IFN-gamma response during the acute phase of the infection, because of its important role as a mediator of host resistance against Toxoplasma as demonstrated in mice, sheep and humans [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%